Differential Expression of Programmed Cell Death on the Follicular Development in Normal and Miniature Pig Ovary - Kim, Sang Hwan; Min, Kwan Sik; Kim, Nam Hyung; Yoon, Jong Taek (PLOS ONE, 2012)
Follicles are important in oocyte maturation. Successful estrous cycle requires remodeling of follicular cells, and proper execution of programmed cell death is crucial for normal follicular development. The objectives of the present study were to understand programmed cell death during follicle development, to analyze the differential follicle development patterns, and to assess the patterns of apoptosis and autophagy expression during follicle development in normal and miniature pigs. Through the analysis of differential patterns of programmed cell death during follicular development in porcine, MAP1LC3A, B and other autophagy-associated genes (ATG5, mTOR, Beclin-1) were found to increase in normal pigs, while it decreased in miniature pigs. However, for the apoptosis-associated genes, progression of genes during follicular development increased in miniature pigs, while it decreased in normal pigs. Thus, results show that normal and miniature pigs showed distinct patterns of follicular remodeling manifesting that programmed cell death largely depends on the types of pathway during follicular development (Type II or autophagy for normal pigs and Type I or apoptosis for miniature pigs).